Simulation of soft switching bi-directional DC/DC converter: article - Abdullah, Ahmad Fahmi (Faculty of Electrical Engineering, 2007)
This paper present the work carried out in developing computer simulation models of soft switching bi-directional DC/DC converter. This converter is composed from a few topologies and is assembled into two symmetrical parts. With the help of inductor and the transformer leakage inductance, ZVS is realized for all switches in the whole load range. Moreover, the diode reverse recovery is also reduced with ZCS and the corporation of a designed pulse-width modulation control. These measures reduce switching losses, voltage and current stresses and electromagnetic interference (EMI). In the theoretical analysis, the switching cycle as well as the operation principle of soft switching is described in detail. Simulation results of 500W model is described to show all the switches of converter can operate in the ZVS condition without requiring any additional circuit components. The simulation models was developed using the MATLAB/Simulink.